Δ9-tetrahydrocannabinol (Δ9-THC) promotes neuroimmune-modulatory microRNA profile in striatum of simian immunodeficiency virus (SIV)-infected macaques - Simon, Liz (J Neuroimmune Pharmacol, 2015)
Cannabinoid administration before and after simian immunodeficiency virus (SIV)-inoculation ameliorated disease progression and decreased inflammation in male rhesus macaques. Δ9-tetrahydrocannabinol (Δ9-THC) did not increase viral load in brain tissue or produce additive neuropsychological impairment in SIV-infected macaques. To determine if the neuroimmunomodulation of Δ9-THC involved differential microRNA (miR) expression, miR expression in the striatum of uninfected macaques receiving vehicle (VEH) or Δ9-THC (THC) and SIV-infected macaques administered either vehicle (VEH/SIV) or Δ9-THC (THC/SIV) was profiled using next generation deep sequencing. Among the 24 miRs that were differentially expressed among the four groups, 16 miRs were modulated by THC in the presence of SIV. These 16 miRs were classified into four categories and the biological processes enriched by the target genes determined. Our results indicate that Δ9-THC modulates miRs that regulate mRNAs of proteins involved in 1) neurotrophin signaling, 2) MAPK signaling, and 3) cell cycle and immune response thus promoting an overall neuroprotective environment in the striatum of SIV-infected macaques. This is also reflected by increased Brain Derived Neurotrophic Factor (BDNF) and decreased proinflammatory cytokine expression compared to the VEH/SIV group. Whether Δ9-THC-mediated modulation of epigenetic mechanisms provides neuroprotection in other regions of the brain and during chronic SIV-infection remains to be determined.